Professional women and family patterns - Gamio de Barrenechea, Nita (2013)
In this article, the author considers the strategies discussed at the Fourth World Conference on Women, held in Beijing, on the incorporation of women into theworkforce without gender discrimination and on promoting their economic rights and their independence in order to make a reflective analysis on the process of adaptation that women must undergo in arder to access the labor market, while harmonizing with their duties as mothers and wives and successfully running their homes and families.